Influencia Del Grado De Acidez, Tiempo Y Temperatura Del Jugo De Limon Sobre La Resistencia A La Corrosion Del Acero Inoxidable Aisi 304 Repasivado Y Expuesto A Una Atmosfera Salina Controlada - Garrido Romero, Litza Maribel (2018)
In recent years there has been particular interest in increasing the chemical properties of stainless steels using organic solutions as is the use of citric acid asreplacement of nitric acid which is harmful and dangerous. In this research the influence of degree of acidity time and temperature a solution of lemon juice over the corrosion resistance of steel AISI 304 repasivado and exposed to a controlled salt atmosphere was evaluated for it specimens previously sanded were placed in a solution of lemon juice for repasivarlas, the variables studied were subjected: acidity (pH): 2.28 (pure lemon juice), 3 and 4; (lemon juice diluted in distilled water), Time: 20 min, 40 min and 60 min; Temperature: 23 (T. ambient), 50 ° C and 75 ° C. Subsequently the specimens already repasivadas were exposed to a saline environment controlled in a salt spray chamber following the Standard B 117for a week. Resultinga remarkable increase in corrosion resistance of stainless steel AISI 304 when repasivado in a solution with an acidity (pH) of 2.28, for a time of 60 min and a temperature of 75 ° C; obtaining a density bite 0.5168 *March 10 pits / m2 and a size of bite 0.1712 mm2 which according to ASTM G 46-94 the specimen category R1,indicating that the probe has a high corrosionresistance. Similarly, statistical analysis ANOVA with F test and concluded that the acidity time and temperature significantly influence the corrosion resistance of stainless steel AISI 304